2014
DOI: 10.1002/cplx.21574
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of organization increase in complex systems

Abstract: This paper proposes a variational approach to describe the evolution of organization of complex systems from first principles, as increased efficiency of physical action. Most simply stated, physical action is the product of the energy and time necessary for motion. When complex systems are modeled as flow networks, this efficiency is defined as a decrease of action for one element to cross between two nodes, or endpoints of motion - a principle of least unit action. We find a connection with another principle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…In contrast, in dissipative systems without an energy source the potential energy is minimized at stationary states. Since its appearance, Prigogine's principle of minimum entropy production has stimulated a lot of critical discussions [6][7][8][9][10][11][12], including Ziegler's conclusion, that entropy production is maximized in nonequilibrium systems [13][14][15][16][17][18]. Several authors suggested that the entropy production is neither maximal nor minimal [19,20].…”
mentioning
confidence: 99%
“…In contrast, in dissipative systems without an energy source the potential energy is minimized at stationary states. Since its appearance, Prigogine's principle of minimum entropy production has stimulated a lot of critical discussions [6][7][8][9][10][11][12], including Ziegler's conclusion, that entropy production is maximized in nonequilibrium systems [13][14][15][16][17][18]. Several authors suggested that the entropy production is neither maximal nor minimal [19,20].…”
mentioning
confidence: 99%
“…The flow of energy during any arbitrary process when coupled with the dimension of time gives rise to the notion of action , formally represented as A=ABfalse(TVfalse)dt=ABfalse(δEfalse)dt=ABL(pi,qi)dt, where the pair, L(qi,pi) is the generalized position‐momentum pair, t is the time, δE is the change in energy along a specific path (in this case AB), T and V are the kinetic and potential energies, respectively, and L(pi,qi), the Lagrangian . There are several interpretations of the Action Principle, for example, the laws of physics when formulated in terms of the Action Principle identify any natural process as the one in which energy differences are leveled off in the least possible time (Maupertius' formulation) ; among all existing possible paths, the path of least action is the one along which a natural process must proceed (Hamiltonian formulation) (Chatterjee, submitted). On the energy landscape, there is a unique trajectory that directs (energy) flows along the lines of steepest descent.…”
Section: Methodsmentioning
confidence: 99%
“…In (dissipative) random dynamical systems [Arnold, 1995], [Crauel and Flandoli, 1994], action is not minimized for each element of the system, but, on average over an ensemble of elements (or repeated trajectories of the same element) [Georgiev and Georgiev, 2002], [Georgiev et al, 2015], [Georgiev and Chatterjee, 2016], [Georgiev et al, 2017]. Obstructive-constraint minimization therefore reduces action for each event within the system and self-organizes it, forming a flow structure that could be construed as a dissipative structure [England, 2015], [Evans and Searles, 2002], [Prigogine, 1978].…”
Section: Least Action Principlesmentioning
confidence: 99%